ANALISIS QUALITY OF SERVICE (QoS) PADA SIMULASI JARINGAN MULTIPROTOCOL LABEL SWITCHING VIRTUAL PRIVATE NETWORK (MPLS VPN) - Ningsih, Yuli Kurnia; Susila, Tjandra; Ismet, Rizky Febrian (Jurnal Teknik Elektro, 2004)
MPLS technology is a new data communication technology that changes the routing processto switching process using label. Thereâs many application that the basics is used MPLS,and one of them is VPN. Using MPLS, VPN will have many benefits like the scalability andsecurity. This paper describes the Quality of Service (QoS) in simulation Virtual PrivateNetwork used Multi Protocol Label Switching. Some parameters that used to increased theQuality of Service is Round Trip Time (RTT) or latency, delay jitter and packet loss.Keywords: QoS, packets, ound trip time, delay,packet lo